PREVENTION OF MASTITIS IN THE DRY PERIOD IN CATTLE - Tul, oleksandra; pareek, chandra shekhar (Translational Research in Veterinary Science, 2023)
Infection of the udder during the dry period can be the cause of mastitis in the postpartum period. Most often, we recorded mastitis in the winter-spring period (8.6–10.2%). Studying the distribution of various forms of mastitis depending on the inflammation of the mammary gland, we most often detected serous mastitis in the farm (51–59%) in the first weeks after parturition. To study the effectiveness of Bovaclox DC Xtra, two groups of cows with 5 heads were created. After the last milking, cows of the experimental group were intracisternal injected with Bovaclox DC Xtra into each quarter of the udder. Before the injection of the preparation, the udder of cows was examined for mastitis by the accepted methods, and the reaction of the secretion of the udder with the California mastitis test was carried out. There were no signs of mastitis in cows of both groups. The udder condition was monitored on the 20th day after drying-off, 10 days before parturition, and 7 days after parturition. 7 days after parturition, a clinical examination of the cows of both groups was carried out. There were no signs of mastitis in the cows of the experimental group. And one cow in the control group had serious mastitis. The treatment was carried out by rubbing the Sanobit preparation into the skin of the udder with simultaneous massage of the udder from the bottom up, holding a short novocaine blockade of the udder nerves according to D. Logvinov. Clinical recovery of the animal occurred after 5 days of treatment.